TESTING DNA VARIATION IN KABULI CHICKPEA SEEDS THROUGH ISSR-PCR - GUPTA, NEHA; BHAGYAWANT, SAMEER SURESH (Innovare Journal of Life Sciences, 2021)
Objective: Chickpea is an annual legume known for its high seed protein thus beneficial for one’s health and well-being. Of the two chickpea seed types, Kabuli seeds have reasonably high-protein and -carbohydrate contents, as a result, set up more commercial demand. Methods: Inter simple sequence repeat (ISSR) markers are useful in the areas of genetic diversity. The present study attempted ISSR-PCR experimentation in testing DNA variation predominantly in Kabuli chickpea seed accessions employing 10 different set of ISSR primers. Results: In vitro amplification by PCR revealed an average number of bands per primer per accession which accounted to 8.7. Maximum number of bands (25) scored by the primer UBC-836 while least number of bands (12) were displayed by UBC-811. Conclusion: The accession JGK-1 and IPCK-12-288 presented divergent DNA polymorphic among all chickpea accessions tested and therefore found distinct. The genetic divergence at DNA level existed between these chickpea accessions can be used proficiently for future plant breeding program.